Selective Adsorption of Anionic Dyes by Graphene Oxide Adsorbent - Amri, Amri; Wibiyan, Sahrul (Indonesian Journal of Material Research, 2024)
Pollution from dyes is well-known for its harmful effects on human health and the environment. Eliminating pollutants such as dyes is a crucial task that can be achieved through various methods, one of which is adsorption. The synthesis of graphene oxide material is achieved from graphite using the Hummers method. The obtained material was then characterised using XRD and FT-IR techniques and tested as an adsorbent for selective adsorption of anionic dyes. The obtained results indicate that the congo red dye was absorbed the most in the selective dyes process, followed by the methyl orange dye, and finally the direct yellow dye.